Dual energy computed tomography evaluation of skeletal traumas. Issue 134 (January 2021) - Simonetti, Igino; Verde, Francesco; Palumbo, Luigi; Di Pietto, Francesco; Puglia, Marta; Scaglione, Mariano; Ragozzino, Alfonso; Romano, Stefania
Abstract: Skeletal traumas are among the most common routine challenges faced by Emergency Radiologists, in particular in case of radiographically occult nondisplaced fractures or in case of soft tissue injuries. With the development of Dual Energy Computed Tomography (DECT) technology, new post-processing applications have gained a useful diagnostic role in many fields of musculoskeletal imaging including acute skeletal trauma imaging. In addition to conventional CT images, DECT allows for the generation of virtual calcium-suppressed images subtracting calcium from unenhanced CT images based on the fact that material attenuation varies at different energy levels. In this way, virtual-non-calcium (VNC) images can precisely characterize traumatic bone marrow edema in both axial and appendicular skeleton, facilitating prompt clinical decision, especially when magnetic resonance method is contraindicated or unavailable. Other DECT emerging applications in the trauma setting include metal artifact reduction and collagen mapping for the evaluation of injuries affecting ligament, tendon, and intervertebral disk. This review focuses on the basic principles of DECT and related post-processing algorithms, highlighting the current advantages and limitations of these new imaging advances in the Emergency Department related to skeletal traumas.